KENDALA MAHASISWA PGSD FKIP USK DALAM MENGIKUTI PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) USK UNGGUL - Siti Wahyu Sunandayani; Numasyitah Numasyitah; Mislinawati Mislinawati (Jurnal Tunas Bangsa, 2023)
Free Learning Independent Campus (MBKM) USK Superior is a new policy launched by Syiah Kuala University to support the national MBKM program. In the implementation of the USK Superior Independent Learning Campus (MBKM), there were many complaints from students because they experienced problems in the implementation process. This study aims to find out what obstacles students experience while participating in the USK Superior MBKM program at assigned schools. This research is a qualitative research with a descriptive research type. The source of the data in this study were 2020 class students who had completed the USK. USK Superior MBKM program. The data collection techniques used were interviews and questionnaires by interviewing 10 students to find out what the student's problems were and distributing questionnaires to 40 students to find out how many students were experiencing problems. The data obtained were then analyzed using qualitative data analysis techniques, namely data reduction (Data Reduction), data presentation (Data Display) and data conclusions/verification (Conclusion Drawing/Verification) as well as questionnaire calculations using Gutman Scale calculations. Based on the results of data analysis, it can be concluded that the students' obstacles in participating in the USK Superior Independent Campus Learning Program (MBKM), namely: (1) Assignments, students are burdened with giving assignments on the web page. (2) School parties who do not support students in implementing the program (3) Students who do not understand the material during the debriefing and do not contribute in groups (4) Fees given at the end of the assignment (5) The program coordinator who is not responsive in responding to student reports. While the results of the analysis of student response data obtained an average of 76.8%, which means that many PGSD FKIP USK students experienced problems when participating in the USK Superior MBKM program.AbstrakMerdeka Belajar Kampus Merdeka (MBKM) USK Unggul merupakan kebijakan baru yang diluncurkan oleh Universitas Syiah Kuala untuk mendukung program MBKM nasional. Dalam pelaksanaan Merdeka Belajar Kampus Merdeka (MBKM) USK Unggul banyak keluhan dari mahasiswa karena mengalami kendala dalam proses pelaksanaannya. Penelitian ini bertujuan untuk mengetahui kendala apa saja yang dialami oleh mahasiswa selama mengikuti program MBKM USK Unggul di sekolah penugasan. Penelitian ini merupakan penelitian kualitatif dengan jenis penelitian deskriptif. Sumber data dalam penelitian ini adalah mahasiswa angakatan 2020 yang telah selesai mengikuti program MBKM USK USK Unggul. Teknik Pengumpulan data yang digunakan adalah wawancara dan angket dengan mewawancarai 10 mahasiswa untuk mengetahui apa saja kendala mahasiswa dan membagikan kuesioner kepada 40 mahasiswa untuk mengetahui seberapa banyak mahasiswa mengalami kendala. Data yang diperoleh kemudian dianalisis menggunakan teknik analisis data kualitatif yaitu reduksi data (Data Reducation), penyajian data (Data Display) dan kesimpulan/verifikasi data (Conclusion Drawing/Verification) serta perhitungan kuesioner menggunakan perhitungan Skala Gutman. Berdasarkan hasil analisis data dapat disimpulkan bahwa kendala mahasiswa dalam mengikuti progam Merdeka Belajar Kampus Merdeka (MBKM) USK Unggul yaitu: (1) Penugasan, mahasiswa terbebani dengan pemberian tugas dilaman web. (2) Pihak Sekolah yang kurang mendukung mahasiswa dalam melaksanakan program (3) Mahasiswa yang kurang memahami materi saat pembekalan serta kurang berkontribusi dalam kelompok (4) Biaya yang diberikan diakhir penugasan (5) Pihak Koordniator program yang kurang responsif menganggapi laporan mahasiswa. Sementara dari hasil analisis data respon mahasiswa mendapatkan rata-rata sebesar 76,8% yang artinya banyak mahasiswa PGSD FKIP USK yang mengalami kendala saat mengikuti progam MBKM USK Unggul.